Azospirillum brasilense affects the antioxidant activity and leaf pigment content of Urochloa ruziziensis under water stress - Lucas Guilherme Bulegon; Vandeir Francisco Guimarães; Jessica Cristina Urbanski Laureth (Pesquisa Agropecuária Tropical, 2016)
Water stress leads to the formation of reactive oxygen species, resulting in degradation of leaf pigments and cell death. This study aimed at assessing the oxidative enzyme activity and photosynthetic pigment content in seeds and/or leaves of Urochloa ruziziensis (syn. Brachiaria) inoculated with Azospirillum brasilense under water stress. Assessments of soluble proteins, chlorophylls a and b and carotenoid contents, as well as the activity of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) enzymes, were conducted at the beginning of the water stress process and also under severe water stress and during plant rehydration. Seed inoculation showed a reduction in the action of SOD, under water stress, with an increase after rehydration. POD exhibited an activity greater than CAT in all the assessments, but it did not differ statistically under severe water stress. CAT activity increased under severe stress in all treatments, particularly for leaf inoculation. Chlorophyll a was slightly degraded, maintaining the levels of the irrigated control, while the chlorophyll b and carotenoid contents, in plants subjected to leaf inoculation with A. brasilense, were higher under water stress. It was concluded that the leaf inoculation of U. ruziziensis with A. brasilense makes the plant more efficient at removing reactive oxygen species and protecting chlorophyll a.